The leadership performance of departmental heads in an institution of higher learning in Malaysia / Md Noh Ab Majid ... [et al.] - Ab Majid, Md Noh; Mohamed Shuhidan, Shazalina; Tahar, Emiza; Abdul Latiff, Sarimah; Abdul Talib, Nurafida (Research Management Institute (RMI), 2010)
Higher learning institutions in Malaysia recently became a subject of scrutiny by stakeholders and the public at large. Its managerial and leadership performance were being assessed through various perspectives. A pilot study was conducted to measure the performance of the heads of department leadership, with an objective to identify factors that drive their leadership performance. One hundredand twenty twofull-time managerial/professional and supervisory staff in Universiti Teknologi MARA (UiTM) Terengganu, Malaysia, participated in this survey. The questionnaire was adopted from an international management survey to measure the effectiveness of the management capability of Malaysian organizations. The results from the survey showed that there were different perceptions between the academic and non-academic staff in UiTM of the ability of the heads of department leadership performance in developing the organization's capability. The survey also concluded that visionary & strategic leadership; and leadership skills & personality traits of these department heads were pivotal in shaping their leadership performance in UiTM Terengganu.